INTERACTIVE FLIPBOOK-BASED DIGITAL STORYBOOKS TO INTRODUCE PERSONAL ORAL HYGIENE FOR YOUNG CHILDREN - Purnamasari, Yayu Mega; Martini; Tania, Dea; Nada, Shy Fany Intan Qotrun; Fathonah, Hanna; Alaydah, Fifi (PG PAUD Universitas Negeri Surabaya, 2025)
This study aims to evaluate the effectiveness of digital storybooks in promoting personal hygiene and toothbrushing among young children. This study employs the research and development (R&D) method. It follows the ADDIE development model, which includes five key stages: analysis, design, development, implementation, and evaluation. This product was created using the Canva and Flipbook applications. The product has been assessed for suitability by media and material experts. This research also involved assessments by five teachers, and to test its effectiveness, the product was tested on five sample students at Khalifah Al-Qolam Kindergarten. Data was collected through questionnaires and observations. The data obtained was analyzed using a quantitative descriptive approach. The research results indicate that the digital storybook learning media is feasible, with a 95% approval rate from subject matter experts and an 85% approval rate from media experts. The teacher response test yielded a 68% approval rate, and the student trial test yielded a 92% approval rate, thereby confirming the product's feasibility and effectiveness for use. Thus, this digital storybook can introduce young children to personal hygiene practices, such as brushing their teeth.